2019
DOI: 10.1038/s41598-019-40425-9
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin Protects Against Cisplatin Ototoxicity by Changing the STAT3/STAT1 Ratio and Activating Cannabinoid (CB2) Receptors in the Cochlea

Abstract: Capsaicin, the spicy component of hot chili peppers activates the TRPV1 pain receptors, and causes rapid desensitization. Capsaicin also ameliorates cisplatin-induced nephrotoxicity. Cisplatin, a commonly used anti-neoplastic agent for solid tumors causes significant hearing loss, nephrotoxicity and peripheral neuropathy. Upregulation of cochlear TRPV1 expression is related to cisplatin-mediated ototoxicity. Here we report that direct TRPV1 activation by localized trans-tympanic (TT) or oral administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 53 publications
(77 reference statements)
1
31
0
Order By: Relevance
“…Moreover, TRPV1 receptors and cannabinoid receptors share some signaling pathways in various cell types [ 30 , 31 , 32 , 33 , 34 , 35 ]. Several groups have demonstrated the activation of TRPV1 receptors by endocannabinoids, so there is a possibility that Capsaicin may activate cannabinoid receptors as well [ 32 , 36 ]. In this way, the effect of Capsaicin was explored after inhibiting CB 1 or CB 2 receptors with specific antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TRPV1 receptors and cannabinoid receptors share some signaling pathways in various cell types [ 30 , 31 , 32 , 33 , 34 , 35 ]. Several groups have demonstrated the activation of TRPV1 receptors by endocannabinoids, so there is a possibility that Capsaicin may activate cannabinoid receptors as well [ 32 , 36 ]. In this way, the effect of Capsaicin was explored after inhibiting CB 1 or CB 2 receptors with specific antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin-associated ototoxicity is a major complication of cisplatin-based chemotherapy (2,3,5). cisplatin-induced (10,(12)(13)(14). The present study demonstrated that cisplatin-induced ototoxicity in Hei-oc1 auditory cells was associated with the inhibition of cell viability and dysregulation of genes related to apoptosis, cell cycle arrest and several pathways, including the p53, HiF-1, Wnt and Pi3K-akt signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Several drugs with antagonistic effects against cisplatininduced cytotoxicity, dna damage, and apoptosis in cochlear hair cells might represent potential treatment strategies for cisplatin-induced ototoxicity (10,(12)(13)(14). For instance, tetramethylpyrazine (Tet) and tanshinone iia (Tan iia) can protect against hearing impairment and ototoxicity induced by aminoglycoside antibiotics, cisplatin, and radiation (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these targets, however, several other EC mechanisms (mainly related to inflammation) are present in the auditory system and in other CNS regions important for tinnitus ( Figure 2 ). A protective EC mechanism is present in the cochlea ( 224 , 225 ). Moreover, animal studies show inflammatory responses in the auditory cortex after tinnitus induction ( 154 , 226 ), and inflammatory responses in the cochlea ( 154 , 227 , 228 ) and cochlear nuclei ( 229 232 ) after tinnitus-inducing treatments.…”
Section: Introductionmentioning
confidence: 99%